The Effect of Organizational Intelligence on Improving the Performance of Bushehr Public Library Staff - Abbas Doulani; mahnaz saadat; Roya Baradar (نشریه مطالعات دانش‌پژوهی)
Purpose: This study aims to explore the impact of organizational intelligence on the performance of public library employees in Bushehr Province.Methodology: This research follows an applied purpose and a descriptive-correlational approach. The population consists of 164 employees from public libraries in Bushehr Province. Given the small size of the population, a census method was applied. Data were collected using two questionnaires: Karl Albrecht's (2003) organizational intelligence scale and an employee performance questionnaire based on the Echio performance model. Data analysis involved Kolmogorov-Smirnov, linear regression, Friedman, and chi-square tests.Findings: The results revealed that organizational intelligence components, such as strategic vision, desire for change, morale, unity and agreement, application of knowledge, common destiny, and performance pressure, are significantly correlated with employee performance in public libraries. Additionally, no significant differences were found regarding demographic variables (gender, education level, and work experience) in relation to the effect of organizational intelligence on employee performance.Conclusion: The study concludes that organizational intelligence significantly influences the performance of librarians in public libraries. Identifying and strengthening the various components of organizational intelligence can enhance library staff performance.Value: This research emphasizes the importance of human resources and highlights the role of organizational intelligence in improving performance, which is particularly relevant in the context of public libraries.